Cardiovascular Disease and Cognitive Decline in Postmenopausal Women: Results From the Women's Health Initiative Memory Study. Issue 6 (18th December 2013) - Haring, Bernhard; Leng, Xiaoyan; Robinson, Jennifer; Johnson, Karen C.; Jackson, Rebecca D.; Beyth, Rebecca; Wactawski‐Wende, Jean; von Ballmoos, Moritz Wyler; Goveas, Joseph S.; Kuller, Lewis H.; Wassertheil‐Smoller, Sylvia
Abstract : Background: Data on cardiovascular diseases (CVD) and cognitive decline are conflicting. Our objective was to investigate if CVD is associated with an increased risk for cognitive decline and to examine whether hypertension, diabetes, or adiposity modify the effect of CVD on cognitive functioning. Methods and Results: Prospective follow‐up of 6455 cognitively intact, postmenopausal women aged 65 to 79 years old enrolled in the Women's Health Initiative Memory Study (WHIMS). CVD was determined by self‐report. For cognitive decline, we assessed the incidence of mild cognitive impairment (MCI) or probable dementia (PD) via modified mini‐mental state examination (3 MS) score, neurocognitive, and neuropsychiatric examinations. The median follow‐up was 8.4 years. Women with CVD tended to be at increased risk for cognitive decline compared with those free of CVD (hazard ratio [HR], 1.29; 95% CI: 1.00, 1.67). Women with myocardial infarction or other vascular disease were at highest risk (HR, 2.10; 95% CI: 1.40, 3.15 or HR, 1.97; 95% CI: 1.34, 2.87). Angina pectoris was moderately associated with cognitive decline (HR 1.45; 95% CI: 1.05, 2.01) whereas no significant relationships were found for atrial fibrillation or heart failure. Hypertension and diabetes increased the risk for cognitive decline in women without CVD. Diabetes tended to elevate the risk for MCI/PD in women with CVD. No significant trend was seen for adiposity. Conclusions: CVD is associated with cognitive decline in elderly postmenopausal women. Hypertension and diabetes, but not adiposity, are associated with a higher risk for cognitive decline. More research is warranted on the potential of CVD prevention for preserving cognitive functioning.